1992
DOI: 10.1097/00004032-199202000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of 222Rn in Domestic Water Supplies to 222Rn in Indoor Air in Colorado Homes

Abstract: The contribution of 222Rn from domestic water wells to indoor air was investigated in a study of 28 houses near Conifer, CO. Air concentrations determined by alpha-track detectors (ATDs) and continuous radon monitors were compared with the predictions of a single-cell model. In many of the houses, the water supply was shown to contribute significantly to levels of indoor 222Rn. The data from the ATD study were augmented with a continuous monitoring study of a house near Lyons, CO. The well water in that house … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The study expands upon work completed in the Front Range of Colorado by students and faculty at the Colorado School of Mines in Golden and researchers at the US Geological Survey in Denver (Lawrence, 1990;Lawrence et al , 1991;Lawrence et al, 1992;Frishman et al 1993;. Folger et al, 1994;Folger, 1995;Folger, et al 1996a;Folger, et al, 1996b).…”
Section: )mentioning
confidence: 81%
See 1 more Smart Citation
“…The study expands upon work completed in the Front Range of Colorado by students and faculty at the Colorado School of Mines in Golden and researchers at the US Geological Survey in Denver (Lawrence, 1990;Lawrence et al , 1991;Lawrence et al, 1992;Frishman et al 1993;. Folger et al, 1994;Folger, 1995;Folger, et al 1996a;Folger, et al, 1996b).…”
Section: )mentioning
confidence: 81%
“…The purpose of this study was to examine the natural processes affecting the distribution and abundance of 222Rn in groundwater. Although there are no clear indications that direct ingestion of 222Rn in water poses a significant risk to human health, 222Rn in well water is known to contribute to high levels of airborne 222Rn in some homes (Prichard, 1987;Lawrence et al , 1992). Airborne 222Rn is thought to cause between 7,000 and 30,000 lung cancer deaths per year in the United States (Puskin, 1992), and is the most significant source of ionizing radiation to which the general public is exposed (Cothern, 1987).…”
Section: Overviewmentioning
confidence: 99%
“…Calmet et al (2011) found out that people may be exposed to radon from water as it degasses from water during handling. Lawrence et al (1992) revealed that in many of the houses, the water supply was shown to contribute significantly to levels of indoor 222 Rn. Hence, further studies are required to understand other routes of entry of radon from water to air, to biomonitor exposure status and to find out ways and means avoid public exposure to water source of radon.…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Nero (1989) reports that when structures are located on soils with large intrinsic permeabilities, extraordinarily high indoor radon concentrations can occur even when the radium content of the soil is low. Other researchers (e.g., Folger et al, 1994;Lawrence et al, 1992) have documented high radon activity in groundwater. The combination of these two factors poses an interesting question of whether degassing of radon from groundwater (i.e., the partitioning of radon from groundwater to the soil gas) may contribute to indoor radon levels, especially when the structures are slightly under-pressurized with respect to atmospheric conditions.…”
Section: Introductionmentioning
confidence: 96%